Analisis Return on Equity, Dividend Payout Ratio, Price to Earning Ratio dan Pengaruhnya Terhadap Return Saham pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia - Samino Hendrianto (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the effect of return on equity, dividend payout ratio, price earnings ratio on stock returns in LQ45 companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2016-2020 period. The sampling technique used purposive sampling technique. Based on purposive sampling obtained 17 companies. The type of data used is secondary data obtained by the Indonesia Stock Exchange (IDX). The analytical method used is panel data regression analysis with the help of software eviews 12.0. The results showed that return on equity had no effect on stock returns. However, the dividend payout ratio has a negative effect on stock returns and the price earning ratio has a positive effect on stock returns.